The Influence of Reading Interest on Student Discussion Activeness in Learning Evaluation Techniques Courses in the Islamic Religious Education Study Program, Singaperbangsa University, Karawang - M Makbul; Ajat Rukajat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research aims to determine the relationship between students' interest in reading and active discussion in the learning evaluation techniques course. This research is a qualitative type of research with an ex post facto approach with a questionnaire research instrument, with the number of respondents being 85 students of Islamic religious education at the University of Singaperbangsa Karawang, the data analysis techniques used were descriptive and inferential analysis. The results of this study revealed that the reading interest of Islamic religious education students was 20% in the low category, 41% in the medium category and 39% in the high category, so that it could be interpreted that the average student reading interest was in the medium category. The activeness of Islamic religious education students' discussions was 32% in the low category, 52% in the medium category and 16% in the high category, so it can be concluded that the average student discussion activity was in the medium category. the value of R Square = 0.885, so it can be interpreted that the influence of interest in reading (X) on the liveliness of discussion (Y) of PAI students at Singaperbangsa Karawang University is 85.5% while 15.5% is influenced by other variables which are not the variables of this study.